Distance-Based Habitat Associations of Northern Bobwhites in a Fescue-Dominated Landscape in Kansas - Brian E. Flock; Philip S. Gipson; Roger D. Applegate; Warren B. Ballard (National Quail Symposium Proceedings, 2017)
Northern bobwhites (Colinus virginianus) have a wide distribution across North America which influences its’ associations with habitats in a variety of landscapes. We used radio-marked bobwhites and Euclidean distance to characterize land cover associations of bobwhites at generalized level 1 and specific level 2 land cover classifications during the reproductive (15 Apr-14 Oct) and covey (15 Oct-14 Apr) periods in southeastern Kansas from 2003 to 2005. Habitat associations occurred during the reproductive (Wilkes’ k 1⁄4 0.04, F6,36 1⁄4 143.682, P , 0.001) and covey (Wilkes’ k 1⁄4 0.056, F6, 29 1⁄4 81.99, P , 0.001) periods. Ranking of the reproductive period habitats indicated bobwhites preferred locations in close proximity to fescue (Festuca spp.) over all other habitats. Coveys preferred locations in close proximity to woody cover. Bobwhites were found to associate with specific habitats at the level 2 land cover classification during the reproductive (Wilkes’ k 1⁄4 0.006, F16, 26 1⁄4 284.483, P , 0.001) and covey (Wilkes’ k 1⁄4 0.004, F16, 19 1⁄4 276.037, P , 0.001) periods. Bobwhites preferred locations in close proximity to fescue pastures and roads equally over all other habitats during the reproductive period. Coveys preferred locations in close proximity to roads and Conservation Reserve Program lands during the covey period. Fescue pastures may be avoided by bobwhites during the covey period, provided adequate cover is not provided, but bobwhites are strongly associated with them during the reproductive period because they meet nesting and brooding needs not met by other habitats.
Keywords: Colinus virginianus; Conservation Reserve Program; Euclidean distance; habitat associations; Kansas; northern bobwhite